2012
DOI: 10.1021/jf2038778
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic Asthma Properties of Brazilin through Inhibition of TH2 Responses in T Cells and in a Murine Model of Asthma

Abstract: This study aimed to determine whether brazilin exhibits anti-inflammatory effects that inhibit T helper cell type II (T(H)2) responses and whether it suppresses allergic inflammation reactions in a murine model of asthma. We found that brazilin inhibited the mRNA and protein expression of interleukin (IL)-4 and IL-5 induced by phorbol myristate acetate (PMA) and cAMP in EL-4 T cells in a dose-dependent manner. Following the intratracheal instillation of brazilin in ovalbumin (OVA)-immunized mice, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Samples were loaded and separated by using 10% Tris-tricine gel with 0.1% gelatin as a substrate. After separation by electrophoresis, the gel was renatured and then incubated with development buffer at 37°C for 48 h. After development, the gel was stained with 0.5% Coomassie blue R-250 for 30 min and then destained appropriately [ 26 ]. The activity of MMP was quantified by using Image J software.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were loaded and separated by using 10% Tris-tricine gel with 0.1% gelatin as a substrate. After separation by electrophoresis, the gel was renatured and then incubated with development buffer at 37°C for 48 h. After development, the gel was stained with 0.5% Coomassie blue R-250 for 30 min and then destained appropriately [ 26 ]. The activity of MMP was quantified by using Image J software.…”
Section: Methodsmentioning
confidence: 99%
“…1) is a compound isolated from the traditional herbal medicine Caesalpinia sappan L. Evidence has indicated that brazilin exhibits multiple biological properties, including anti-hepatotoxicity [16], anti-tumor [17], anti-platelet [18], anti-oxidant [19], immune system modulatory activities [20], and anti-inflammatory activities [21,22]. Furthermore, many studies have shown that brazilin is involved in the regulation of either NF-κB or activator protein 1 (AP-1) activation [19,23].…”
Section: Introductionmentioning
confidence: 99%
“…Because allergic asthma is a Th2-mediated inflammatory disease, theoretically, substances that exhibit antiinflammatory and/or Th1-skewing properties could potentially be used to ameliorate the disease. Numerous herbs, phytochemicals, and vitamins have been investigated for their interactions with the immune system and used as complementary and alternative medicines in treating atopic disorders (Chang et al 2013; Chang et al 2011; Hwang et al 2012; Lee et al 2012a; Lee et al 2010; Lee et al 2012b; Mainardi et al 2009; Rao et al 2013; Wang et al 2013). Ganoderma is a medicinal fungus that is considered to be a therapeutic biofactory with numerous pharmacologically active components (Paterson 2006).…”
Section: Discussionmentioning
confidence: 99%